Single-shot electrical detection of short-wavelength magnon pulse transmission in a magnonic thin-film waveguide - Moojune Song; Jinho Lim; Wei Zhang; Dmytro A. Bozhko; Ralu Divan; Axel Hoffmann; Kab-Jin Kim; Valentine Novosad; Yi Li (npj Spintronics)
Abstract The advance of magnon spintronics requires understanding of time-domain magnon pulse transmission in order to develop high-speed information processing protocols. In this work, we demonstrate single-shot electrical detection of narrow-band magnon pulse transmission in a yttrium iron garnet thin-film delay line. The high signal-to-background ratio of magnon transmission band allows us to directly probe the magnon transmission electrically using a fast oscilloscope and to study its spectral evolution using Fast Fourier Transform (FFT) of the time-domain transmitted signal. At elevated input power, we show a magnon transmission reduction and a spectral distortion, which can be understood by the nonlinear magnon excitation in the transmission band defined by the antenna geometry. In addition, we also find that the higher- (lower-) frequency magnon spectral component exhibits a lower (higher) magnon group velocity, showing a dispersion agreeing with the Damon-Eshbach dependence. Our results provide important guidance of magnon pulse engineering for their applications in spin wave computing and coherent magnon information processing.